BUDAYA PESANTREN DI PULAU SERIBU MASJID, LOMBOK - Fahrurrozi Fahrurrozi (Karsa: Journal of Social and Islamic Culture, 2015)
Lombok, an island in West Nusa Tenggara (NTB) province, known as "the island of a thousand mosques" is an area that is predominantly Muslim. The presence of Islam embraced by the majority of people in Lombok Island is not only characterized by a high public enthusiasm in building places of worship such as mosques and prayer room (mushalla), but also the presence of many pesantrens (Islamic boarding schools). It is reported that there are no less than 300 boarding schools spread across this small island. The existence of the boarding schools in Lombok is not merely as formal and non-formal institutions, they also play an important role in the dynamic of Islamic society. Pesantren has served: 1) as the transmission center of Islamic knowledge; 2) to maintain the continuity of Islamic tradition; and 3) as the center of the production of Islamic scholars.Traditions played by pesantren communities in Lombok looks so firmly, they preserve the identity of indigenous localites where they are located. this is what is typical and unique in studying pesantren and its dynamic in society. It is how the culture of pesantren in the island of thousands of mosques is which is the primary focus of this paper.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.730